Early Pleistocene freshwater fish from Dursunlu (Ilgın Basin, south-western Türkiye): Implications for early hominin dispersals out of Africa - Àngel Blanco-Lapaz; Àngel H. Luján; Elvan Demirci; Josep Sanjuan (Quaternary Environments and Humans)
Dursunlu, located in the Ilgın Basin (south-western Türkiye), represents one of the most prolific sites to explore early human occupations in Anatolia. This paper describes the lacustrine fish assemblage from this site during the Early Pleistocene (Günz glaciation). The fish community comprised two families, namely Cyprinidae and Cobitidae. Within the cyprinids, the genera had a wide range of ecological diversity. The most frequently observed genera in Dursunlu are Chondrostoma and Squalius, but Capoeta and Barbus are also present. These genera prove that a very shallow and well-oxygenized paleolake occupied the Ilgın Basin with a dense palustrine vegetation belt and partially rocky-gravelly substrate. This paleolake constituted a hotspot for the presence and early dispersal out of Africa of the genera Homo in this region and Eurasia during the Lower Paleolithic/Early Pleistocene.